2008
DOI: 10.2353/ajpath.2008.070876
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Autophagy Prevents Hippocampal Pyramidal Neuron Death after Hypoxic-Ischemic Injury

Abstract: Neonatal hypoxic/ischemic (H/I) brain injury causes neurological impairment, including cognitive and motor dysfunction as well as seizures. However, the molecular mechanisms regulating neuron death after H/I injury are poorly defined and remain controversial. Here we show that Atg7, a gene essential for autophagy induction, is a critical mediator of H/Iinduced neuron death. Neonatal mice subjected to H/I injury show dramatically increased autophagosome formation and extensive hippocampal neuron death that is r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
388
1
5

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 449 publications
(419 citation statements)
references
References 60 publications
(94 reference statements)
24
388
1
5
Order By: Relevance
“…Chronic myocardial ischemia/reperfusion injury induces autophagy increment and apoptosis decrement [9]. Inhibition of autophagy prevents neuron death after hypoxic-ischemic injury in neonatal mice [10]. However, in acute kidney injury (AKI), the association between autophagy and cell death is not obvious.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic myocardial ischemia/reperfusion injury induces autophagy increment and apoptosis decrement [9]. Inhibition of autophagy prevents neuron death after hypoxic-ischemic injury in neonatal mice [10]. However, in acute kidney injury (AKI), the association between autophagy and cell death is not obvious.…”
Section: Discussionmentioning
confidence: 99%
“…In cancer cells, autophagy inhibited starvation-induced apoptotic death (Boya et al, 2005) and also necrotic cell death, especially in conjunction with a block in apoptosis (Jin and White, 2007;Karantza-Wadsworth et al, 2007). Conversely, autophagy was required for necrotic death of neuronal cells in C. elegans (Samara et al, 2008), for stress-mediated necrosis in apoptosis-deficient BaxÀ/ÀBakÀ/À mouse embryonic fibroblasts (MEFs) (Shimizu et al, 2004;Ullman et al, 2008) and loss of autophagy through deletion of Atg7 rescued neurons from death after hypoxia/reperfusion (Koike et al, 2008). Resolving the relationship between autophagy and apoptosis is especially complex, as both are induced by similar stimuli and impact on each other's functions (Maiuri et al, 2007c;Levine et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…9,25,26 Previous studies including ones from our laboratory have demonstrated that hypoxia can induce autophagy, triggering either a cell survival or cell death response depending upon the context. [27][28][29][30][31][32][33][34][35][36][37][38] A recent study demonstrates that autosis, possibly a subtype of autophagic cell death, is induced by hypoxia-ischemia treatment. 39,40 The mechanism governing whether autophagy contributes to cell survival or to cell death is still not well understood, and whether there is a tipping point between these 2 events is unknown.…”
Section: Introductionmentioning
confidence: 99%